Adverse prognostic value of supernormal left ventricular force noninvasively assessed by resting transthoracic echocardiography in hypertrophic cardiomyopathy. (4th February 2022) - D"alfonso, MG; Tesic, M; Peteiro, J; Palinkas, ED; Re, F; Losi, MA; Palinkas, A; Cruz, I; Torres, M A R; Van De Heyning, CM; Djordjevic-Dikic, A; Mori, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Stress Echo 2030 study group of the Italian Society of Echocardiography and Cardiovascular Imaging (SIECVI). Background The excessive cross-bridging of cardiac myosin and actin, resulting in increased left ventricular (LV) force development, is one of the biomechanical abormalities inhypertrophic cardiomyopathy (HCM). Purpose: To assess the prognostic value of increased LV force development at rest in patients with HCM Methods: We enrolled 918 HCM patients (age 48 ± 16 years, 502 males, New York Heart Association I or II, Class III in 48 patients, 6% and with LVOTG >30 mmHg in 211patients, 23%) with ejection fraction (EF) ≥50%, referred for rest transthoracic echocardiography (TTE) in 10 quality-controlled labs from 7 countries (Belgium, Hungary, Italy, Portugal, Serbia, Spain, Brazil). The maximal wall thickness was 21 ± 5 mm. TTE assessment included left ventricular outflow tract gradient (LVOTG, mmHg), EF (%), and LV force (systolic arterial pressure + LVOTG/LV endsystolic volume assessed with 2-D, mmHg/mL). All patients were followed-up. An age- and gender matched control group of 95 healthy subjects was also evaluated. Results.   Compared to normals, HCM showed higher values of EF (68 ± 8 vs 65 ± 5%, p < 0.001) and force (7.2 ± 5.5 vs 4.0 ± 1.8 mmHg/mL, p < 0.001). At a median follow-up of 94 months [interquartile range 40-140 months], 95 all-cause deaths occurred. Mortality was significantly increased in the force highest quartile compared to other quartiles (see figure). At multivariable Cox analysis, increased Force (highest quartile >8.5 mmHg/mL hazard ratio= 2.189 95% CI = 1.095-4.377, p = 0.027 and the intermediate quartile: Force 5.7-8.5 mmHg/mL hazard ratio= 2.525 95% CI = 1.2205.228, p = 0.013) were independent predictors of mortality with age (hazard ratio= 1.065 95% CI = 1.047-1.084, p < 0.001) and maximal wall thickness (hazard ratio= 1.094, 95% CI = 1.055-1.135, p < 0.001). At univariate analysis neither LVOTG (hazard ratio= 1.430, 95% CI = 0.920-2.222, p = 0.112) nor quartiles of EF (hazard ratio= 1.497, 95% CI = 0.868-2.582, p = 0.147) were significant. Conclusion: HCM patients with preserved baseline LV function and higher values of resting LV force ("too good to be normal") show a worse survival, highlighting the dark prognostic side of an excess of force. The hypercontractile phenotype possibly indicates an increased activity of myosin resulting in increased force production at the sarcomere and cellular levels that propagates at the whole-organ level with unfavorable long-term effects on outcome. Figure: Mortality rate based on quartiles of resting LV Force in HCM.